Thinking about provincialism in thinking - Brzechczyn, Krzysztof, 1963-; Paprzycka, Katarzyna.; Nowak, Leszek. (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2012)
The volume addresses a problem rarely discussed by philosophers - the question of provincialism in science (in the broadest sense of the term). There are only a few great centers of science, which attract funding and provide almost ideal opportunities for research and development. They also attract some of the best researchers. Some - but not all. For a variety of reasons, some of the best researchers, or ones who have that potential, may do science outside these centers, in the provinces. The volume is devoted to the problems they face. What is an intellectual province? Who are the provincial thinkers? What is the mark of provincialism? Do provincial (or central) thinkers have any special duties? Are there ways of overcoming one's own provincialism? The authors address these questions across different disciplines, cultures, locations and time periods.